تفسیرِ قرآن کا ادبی و بیانی منہج اور مدرسہ بیانیہ کا کردار: ایک تنقیدی مطالعہ - Mubashar Hussain; Jamil Akhtar (Pakistan Journal of Islamic Research, 2019)
The 20th century Egypt witnessed several methodological approaches to the interpretation of the Quran. One of them, namely the bayāniya school of tafsir (i.e., the Quranic exegesis), received its first blow during the life span of Amīn al-Khūlī, a 20th century Egyptian exegete, who contributed to the Quranic sciences from several important respects. His legacy continued by his several competent deciples including Aysha Bint-e Shāti and Muhammad Ahmad Khalf Allah. The main focus of the said school was two folds: 1), the al-tafsir al-mawdui (i.e., the subject-wise method of interpretation) of the Quran must be observed; and 2), since the Quran is revealed in the Arabic language, its linguistic dimension should be exhaustively followed in its interpretation, in particular, in case of disagreement of the exegetes, because it is the sole criterian to settele the disagreement. Thus, the school maintained that only the full command of the Arabic language can guide the exegetes to reach the true and deeper meaning of the Quranic text. This paper sheds light on the methodological approach articulated by the Bayāniyah School in order to distinguish them from the traditional prevailing interpretive approaches in the domain of tafsir. It also examines to what extent the said school has employed the Prophetic traditions as a primary source of the interpretation of the Quran.